The Scope for Pavement Porters: Addressing the Challenges of Last-Mile Parcel Delivery in London. Issue 9 (December 2018) - Allen, Julian; Bektas, Tolga; Cherrett, Tom; Bates, Oliver; Friday, Adrian; McLeod, Fraser; Piecyk, Maja; Piotrowska, Marzena; Nguyen, ThuBa; Wise, Sarah
The UK parcel sector generated almost £9 billion in revenue in 2015, with growth expected to increase by 15.6% to 2019 and is characterized by many independent players competing in an "everyone-delivers-everywhere" culture leading to much replication of vehicle activity. With road space in urban centers being increasingly reallocated to pavement widening, and bus and cycle lanes, there is growing interest in alternative solutions to the last-mile delivery problem. We make three contributions in this paper: firstly, through empirical analysis using carrier operational datasets, we quantify the characteristics of last-mile parcel operations and demonstrate the reliance placed on walking by vehicle drivers with their vans being parked at the curbside for on average 60% of the total vehicle round time; secondly, we introduce the concept of "portering" where vans rendezvous with porters who operate within specific geographical "patches" to service consignees on foot, potentially saving 86% in driving distance on some rounds and 69% in time; finally, we highlight the wider practical issues and optimization challenges associated with operating driving and portering rounds in inner urban areas.